Transport as a location factor: new start-ups and relocations in Portugal - Adelheid Holl (European Regional Science Association (ERSA), 2002)
This paper analyses the spatial pattern of manufacturing plant location and relocation using municipality data in Portugal from 1986 to 1997. Over this period most of the Portuguese motorways have been constructed extending the network from just about 200 kilometres at the beginning of the 1980s to over 1,300 kilometres by 1998. This is an interesting development that offers opportunities to explore the role of road infrastructure and its improvements as a location factor. In addition to location determinants widely used in the literature, fine measures of motorway access and road accessibility calculated with GIS methodology are included in panel data estimations. Because plant birth and plant relocation result from two different spatial decision processes in the firm they are treated separately. The present study puts these two events in a dynamic context of the plant life cycle and finds evidence that fits with notions of business dynamics. Plant start-ups are positively influenced by the existence of a local pool of potential entrepreneurs, lower wage costs and a more diversified economic environment. Relocations, on the other hand, prefer areas with a greater availability of producer services and an already larger industrial share. These findings suggest that plant relocations, which are at a later stage of the plant life cycle, add to concentration and geographic specialisation, whilst first locations are primarily influenced by the availability of general inputs and cheap factors of production. A key finding of this paper is that road infrastructure matters for both, but more so for plant relocations. Relocations show a considerably larger attraction towards the new road transport corridors. This indicates that as firms grow, their spatial requirements change to accommodate a greater need for high-quality transport infrastructure to sell output over, and get inputs from, a wider geographic area.
Keywords: 330